Occupation and collaboration during in Lithuania during Second world war - Jegelevičius, Sigitas (Genocidas ir rezistencija, 2003)
During the Second World War, Poland was occupied by either the Nazis or the Soviets. The exception to this rule is eastern Lithuania, which was occupied twice by the Soviets. The situation in Lithuania at that time was much more complex. Lithuania was under Soviet occupation. After six weeks of occupation, Lithuania’s territory was annexed to the Soviet Union with the help of collaborators of various nationalities. The state of Lithuania ceased to exist. Then the German occupation followed. This article makes a general comparison between the two occupying powers and the relationship of the Lithuanian population to them.